Importance of Both Innate Immunity and Acquired Immunity for Rapid Expulsion of S. venezuelensis - Yasuda, Koubun; Matsumoto, Makoto; Nakanishi, Kenji (Frontiers in Immunology, 2014)
In the first part of this review, we described the relevant roles of endogenous IL-33 for accumulation of ILC2 and eosinophils even in the lungs of Rag2-/- mice. ATII cells express IL-33 in their nucleus and infection with S.venezuelensis induces IL-33 production by increasing the number of ATII cells possibly by the action of chitin. IL-33 from ATII cells induces ILC2 proliferation and at the same time activates them to produce IL-5 and IL-13, which in combination induce lung eosinophilic inflammation, aiding to expel infected worms in the lungs. In the second part, we showed that, although AID-/- mice normally develop Th2 cells and intestinal mastocytosis after infection with S.venezuelensis, they need adoptive transfers of immune sera from S.venezuelensis-infected mice to obtain the capacity to promptly expel S.venezuelensis. Thus, intestinal nematode infection induces various Th2 immune responses (eg., Th2 cell, ILC2, goblet cell hyperplasia, intestinal mastocytosis, smooth muscle cell contraction, local and systemic eosinophilia and high serum level of IgE and IgG1). However, all of them are not necessary for rapid expulsion of intestinal nematodes. Instead, some combinations of Th2 immune responses are essentially required.